Surface modification of Ni–Ti alloys for stent application after magnetoelectropolishing - Gill, Puneet (Mater Sci Eng C Mater Biol Appl, 2015)
The constant demand for new implant materials and the multidisciplinary design approaches for stent applications have expanded vastly over the past decade. The biocompatibility of these implant materials is a function of their surface characteristics such as morphology, surface chemistry, roughness, surface charge and wettability. These surface characteristics can directly influence the material's corrosion resistance and biological processes such as endothelialization. Surface morphology affects the thermodynamic stability of passivating oxides, which renders corrosion resistance to passivating alloys. Magnetoelectropolishing (MEP) is known to alter the morphology and composition of surface films, which assist in improving corrosion resistance of Nitinol alloys. This work aims at analyzing the surface characteristics of MEP Nitinol alloys by scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS). The wettability of the alloys was determined by contact angle measurements and the mechanical properties were assessed by Nanoindentation. Improved mechanical properties were observed with the addition of alloying elements. Cyclic potentiodynamic polarization tests were performed to determine the corrosion susceptibility. Further, the alloys were tested for their cytotoxicity and cellular growth with endothelial cells. Improved corrosion resistance and cellular viability were observed with MEP surface treated alloys.